2018
DOI: 10.3390/molecules23092184
|View full text |Cite
|
Sign up to set email alerts
|

Dihydromyricetin as a Functional Additive to Enhance Antioxidant Capacity and Inhibit the Formation of Thermally Induced Food Toxicants in a Cookie Model

Abstract: Recently, there is a growing interest in fortifying food products with flavonoids to enhance health benefits. Naringenin, naringin, hesperetin, and dihydromyricetin are four typical flavonoids constituting a natural part of our diet. In the present work, they were fortified into a chia oil cookie model to evaluate their thermal stability during baking as well as their impact on antioxidant capacity and toxicant formation. Among them dihydromyricetin was the most unstable one (only 36.1% of which was left after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…It was reported that phenolic compounds could decrease the CML content of foods in different situations (80) . In a study of Teng et al (81) , it was demonstrated that cookies (baked at 180°C for 20 min) fortified with naringenin, naringin, hesperetin and dihydromyricetin had lower levels of CML and fluorescent AGE.…”
Section: Advanced Glycation Endproduct Content Of Pastry Productsmentioning
confidence: 99%
“…It was reported that phenolic compounds could decrease the CML content of foods in different situations (80) . In a study of Teng et al (81) , it was demonstrated that cookies (baked at 180°C for 20 min) fortified with naringenin, naringin, hesperetin and dihydromyricetin had lower levels of CML and fluorescent AGE.…”
Section: Advanced Glycation Endproduct Content Of Pastry Productsmentioning
confidence: 99%
“…DMY has been reported to inhibit the formation of these harmful substances, for example, formation of several types of genotoxic HAAs in fried beef patties [138]. Likewise, the fortification of DMY in cookies resulted in a pronounced reduction in lipid and protein oxidation as well as AGEs production [139]. Furthermore, the addition of vine tea extract significantly enhanced the sensory features of bread.…”
Section: Dmy Applications In Food Industriesmentioning
confidence: 99%
“…At different concentrations of synthetic silver nanoparticles (0.01–0.1 mg/mL), the free radical scavenging rate was about 56–92%. Recently inclusion of DMY with cyclodextrins 39 and cookie fortified with DMY 40 has been reported for its enhanced antioxidant potential. DMY significantly lowered oxidation compared to control in the previous study, 3 and in the present study, the antioxidant potential was further improved by DMY-mediated AgNPs.…”
Section: Resultsmentioning
confidence: 99%
“…At different concentrations of synthetic silver nanoparticles (0.01-0.1 mg/ mL), the free radical scavenging rate was about 56-92%. Recently inclusion of DMY with cyclodextrins 39 and cookie fortified with DMY 40 has been reported for its submit your manuscript | www.dovepress.com…”
Section: Antioxidant Activitymentioning
confidence: 99%